Analysis of Dynamic Inertia Forces at Main Bearing of Ship Reciprocating Engines - Zubaydi, A. Zubaydi; Ariana, M. Ariana; Baliwangi, L. Baliwangi; Masroeri, A. A. Masroeri; Louhenapessy, F. Louhenapessy; Tukan, M. Tukan; Taribuka, S. M. Taribuka (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
During operation, a ship reciprocating engine will vibrate due to the force resulting from the cycle movement of the dynamic components. Soon or later, the vibration will cause wear of engine components. Therefore, the cause of vibration should be early identified so that the propagation of wear can be anticipated. The study modeled the ship reciprocating engine as a two stroke engine, and analyzed one of the causes of the engine vibration, i.e. the force acting on main bearing, using a numerical simulation. An experimental study was also carried out for measuring the acceleration of vibration response due to the numerical dynamic inertia force. The results showed that the dynamic inertia force acting on the main bearing is the main cause of the vibration of engine.